Does partial quantity rationing of credit affect the technical efficiency of dairy farmers in Punjab, Pakistan?: An application of stochastic frontier analysis. Issue 2 (5th February 2018) - Mehmood, Yasir; Rong, Kong; Bashir, Muhammad Khalid; Arshad, Muhammad
Abstract : Purpose: The purpose of this paper is to empirically investigate the effect of partial quantity rationing of credit on the technical efficiency of dairy farmers in the Punjab province of Pakistan. Design/methodology/approach: Prior to the field survey, the authors constructed a theoretical model for clear identification of partial quantity rationed dairy farmers. Data from 154 dairy farmers were collected that represented three districts of the province. The collected data were analyzed in two stages: first, the efficiency level of dairy farmers was estimated using a stochastic frontier approach; second, the authors employed an inefficiency-effects model to estimate the effect of partial quantity rationing of credit on technical efficiency. Findings: The results revealed that education level of the household head, cross-breed and imported cattle, and electric chaff cutter, all had significant positive impacts on technical efficiency, followed by diversified sources of income. Conversely, the analysis of our key variables, interest rate on principal amount and partial quantity rationing of credit had significant negative effects on the technical efficiency of dairy farmers in selected districts of the Punjab province in Pakistan. Originality/value: The study will be an important contribution to the existing credit constraints and technical efficiency literature and will particularly help the rural financial institutions in terms of approving the loan amount according to the actual requirements of the borrowers. The study's findings and subsequent recommendations will be useful for policy makers in achieving the actual production level, bringing down the poverty levels and ensuring food security in the country.